(untitled) (Pedagogy of Higher and Secondary Education, 2009)
The article touches upon the importance of developing students‘ creativity аs an essential part of forming an educated, creative personality, his/her intellectual potential, proses the importance of pedagogical and psychological aspects of developing the students’ creativity as a driving force for improving the creative potential of students.